The Development of Youth’s Artistic Communication Under the Influence of the Development of Science and Information and Communication Technologies - Bute, Daina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Due to the development of the ICT a new type of student is created. These students are no more passive users of the system of eduaction, they are creating it themselves. Under the influence of the ICT, students use signs, icons and symbols in their everyday communication. The aim or the research - The influence and significance of the information and communication technologies on the development of youth’s artistic communication and creation of new signs. It has been observed that visual perception dominates for majority of people. This is also the reason why visual images and symbols have served as means of communication in the history of human development. Nowadays, numbers, letters and their combinations that contain special meaning and iconic signs are often used in students’ everyday communication. The ICT have brought some changes in students’ perception of the world. The experiment, made in the Art lesson by questioning the first graders, showed that existing ideas about the styles of art that children like at this age are in the contraversion with reality.